2021
DOI: 10.3390/jcm10163701
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Readmission Rates after Takotsubo Syndrome with or without Malignancy: A Nationwide Readmissions Database Analysis

Abstract: The association between malignancy and readmission after Takotsubo syndrome (TTS) hospitalization has not been fully described. We sought to examine the rates, cause, and cost of 30-day readmissions of TTS, with or without malignancy, by utilizing Nationwide Readmissions Databases from 2010 to 2014. We identified 61,588 index hospitalizations for TTS. TTS patients with malignancy tended to be older (70.6 ± 0.2 vs. 66.1 ± 0.1, p < 0.001), and the overall burden of comorbidities was higher than in those witho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…These findings highlight the fact that an optimal medical treatment of TTS is of particular concern when patients suffer from comorbidities such as malignancy and are therefore at higher risk of readmission. Jang et al examined the rates, causes, and costs of 30-day readmissions of TTS, with or without malignancy, by utilizing Nationwide Readmissions Databases from 2010 to 2014 [ 14 ]. The authors identified 61,588 patients with TTS and showed that those with malignancy tended to be older and with a higher overall burden of comorbidities than those without malignancy.…”
mentioning
confidence: 99%
“…These findings highlight the fact that an optimal medical treatment of TTS is of particular concern when patients suffer from comorbidities such as malignancy and are therefore at higher risk of readmission. Jang et al examined the rates, causes, and costs of 30-day readmissions of TTS, with or without malignancy, by utilizing Nationwide Readmissions Databases from 2010 to 2014 [ 14 ]. The authors identified 61,588 patients with TTS and showed that those with malignancy tended to be older and with a higher overall burden of comorbidities than those without malignancy.…”
mentioning
confidence: 99%